Do Cover Crops Influence In Situ Soil Water Potential After Termination? - Olivia M. Peters; Samuel I. Haruna (Agronomy)
Soil water movement is energy-dependent and is influenced by various management practices. It can be understood by measuring the soil water potential (SWP); however, the influence of cover crops (CCs) on SWP is not currently well understood. The objective of this study was to assess the effects of CCs on SWP before and after termination in order to understand their effects on soil water availability for the subsequent cash crop. The experimental design was a completely randomized design with two levels of CCs (CCs vs. no cover crop [NC]) with three replicates. The SWP sensors were buried at 0–10, 10–20, and 20–30 cm depths before CCs were planted. Additionally, soil samples were collected at the aforementioned depths just before CC termination for soil organic carbon (SOC), bulk density (BD), and saturated hydraulic conductivity (Ksat) analysis. Results showed that CCs increased SOC and Ksat, and significantly lowered BD compared with NC management. Before termination, CC plots had significantly lower SWP values compared with NC management, suggesting that the transpirational needs of the CCs can lead to lower water content. After termination, CC management also resulted in lower SWP, suggesting that CCs can increase water-use efficiency by improving soil health parameters. However, effective planning is required for CC implementation, especially in semiarid and arid regions.